THE EFFECT OF QUANTUM LEARNING ASSISTED BY AUDIO VISUAL ON THE SELF EFFICACY OF FIFTH GRADE STUDENTS - Ni Luh Ayu Nita Darmayanti; I Gusti Ayu Tri Agustiana; Adrianus I Wayan Ilia Yuda Sukmana (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine the effect of the quantum learning model assisted by audio visual media on the self efficacy of fifth grade student in social studies subject in Elementary School at Gugus III Tembuku, Bangli in the academic year 2019/2020. This research was a quasi experimental study with a nonequivalent posttest only control grup design. The populations in this study were all fifth grade students of Gugus III Tembuku, Bangli in the academic year 2019/2020 with 186 students. The research sample consisted of 34 students in grade 5 of SD Negeri 5 Yangapi as an experimental grup and fifth grade students of SD Negeri 1 Yangapi as a control group with 26 students. This research used data collection methods with non test techniques. The non-test technique used was a questionnaire to look for self-efficacy data for fifth grade students in social studies subjects. The data of this study were analyzed with descriptive analysis techniques and inferential statistics (t-test). The average acquisition of the experimental group questionnaire was 98, while the average results of the control group questionnaire was 89, 96. Based on the significance level of 5% and dk = 58, it was obtained ttable = 2.001 while the value of tcount = 4.935. So tcount> ttable which proved that H0 is rejected and H1 was accepted. Thus, it can be concluded that there was an influence of the quantum learning model assisted by audio visual media on the self efficacy of Grade 5 students in Social Sciences of Elementary School Gugus III Tembuku, Bangli in the academic year 2019/2020.